UNIVERSITY REFORM TODAY - MARGA, Andrei (2007)
Today education is a pre-condition of the achievements of individuals and communities. Therefore,serious reflection upon education nowadays has a larger impact than ever before. Additionally, the countriesin South-Eastern Europe must break the vicious circle in which reforms are postponed because the educational premises, which in turn depend on economic and administrative reforms, are not met. The only way out is to accelerate the reform of education, an imperative action whichrequires conceptual clarifications, well elaborated programmes, and effective systemic changes. Petty politics of any colour is against a healthy reform of education.The volume University Reform Today represents an effort to answer problems and dilemmas that universities face at this time from a practical perspective. This effort has been connected with the actions of reform in which I have participated as a scholar, a Dean of a Faculty of socialsciences (1990-1992), a Rector of a large university (1993-), a Minister of National Education of Romania (1997-2000), and a member on the Board of the European University Association (2001-).The present volume gathers studies, programmes, analyses, and proposals that I have elaborated and spearheaded in the last decade. [...]